(untitled) (Journal of Musikot Campus, 2025)
This action research investigates the effectiveness of pedagogical interventions in enhancing the teaching and learning of trigonometry among fourth-semester Bachelor of Education (B.Ed.) students at Mid-Western University. Recognizing the abstract nature and practical importance of trigonometry, the study sought to address persistent challenges faced by students, including conceptual confusion, lack of engagement, and poor academic performance. The research was conducted using a cyclical action research framework encompassing three phases: identification, planning, and implementation. Initial diagnostic assessments revealed significant gaps in students’ understanding of trigonometric identities, graphs, and applications. In response, a series of interventions were implemented, including active learning strategies, formative assessments, visual teaching aids, and repetition of key lessons. Data were collected through pre- and post-tests, classroom observations, student feedback, and teacher reflection journals. Post-intervention results demonstrated substantial improvements in students’ academic performance, conceptual clarity, and classroom participation. The findings support the application of constructivist, feedback-oriented, and student-centered pedagogies in mathematics education. The study concludes that systematic, reflective, and evidence-based teaching strategies can significantly improve trigonometry instruction at the higher education level. Moreover, the action research approach facilitated professional growth for the instructor and fostered a more responsive learning environment. This study offers practical insights for mathematics educators and institutions seeking to improve learning outcomes in abstract mathematical domains